Teoria de controle ótimo aplicada a sistemas quânticos abertos - Fernandes, Marllos Eustáquio Fonseca (2023)
This thesis, grounded in the field of quantum computing, explores diverse and crucial topics for the advancement of this area. Firstly, we introduce an innovative "double-bang" solution using optimal control theory for state preparation in the context of quantum teleportation. Combined with the adiabatic door teleportation protocol, this approach provides an experimentally viable way for the implementation of universal quantum computing. Subsequently, we shift our focus to adiabatic quantum computing, revealing the robustness of the adiabatic entanglement protocol to noise and proposing enhancements to the teleportation protocol through the inclusion of local control fields. Collectively, these studies contribute to the progress of quantum computing, offering practical insights for future implementations in Noisy Intermediate-Scale Quantum (NISQ) devices. Finally, we apply the Krotov method to find optimized controls in open quantum systems, highlighting the effectiveness of non-unitary optimization in state preparation, although unitary optimization often proves equivalent in the implementation of quantum gates.